Diane Nguyen’s Literacy As Individualism and Its Impact on Interpersonal Relationships in BoJack Horseman (2014-2020) - Susi Laksmita Pratiwi; Much. Koiri (Journal of English Language and Education, 2026)
Literacy is often understood not merely as a set of technical skills, but as a practice closely tied to identity and personal experience. In BoJack Horseman (2014-2020), this understanding is reflected through the character of Diane Nguyen, whose writing functions as a means of self-construction.  This study examines how Diane’s literacy practices align with the concept of literacy as individualism and how they influence her interpersonal relationships. Using textual and visual analysis approaches, selected scenes across all six seasons are analysed through Williams and Zenger’s concept of literacy as individualism and Sullivan’s interpersonal theory. The analysis focuses on Diane’s writing practices and its impact on her relationships with other characters. The findings show that Diane’s literacy practices reflect the concept of literacy as individualism since they are closely tied to emotional struggle, authenticity, and personal experiences. However, these practices also create tension, misunderstanding, and emotional distance in her relationships.